Prostitution Laws in Malaysia, 1916–1973: A Historical Perspective (Kanun: Jurnal Undang-undang Malaysia, 2025)
Laws concerning prostitution are crucial for regulating such activities, yet an in-depth examination of these laws remain inadequate. Many aspects of these regulations have yet to be thoroughly explored and debated. This study examines prostitution laws in Malaysia by analysing primary and secondary sources, including acts, written reports by the Islamic Religious Council and Malay Customs of Kelantan, journals, books, and theses. The discussion is divided into two parts. The first part examines the types of acts implemented in Malaysia to regulate prostitution activities, with a particular focus on the Women and Girls Protection Act 1973, its strengths and weaknesses, and other related acts. The second part explores the types of laws used to regulate prostitution in Kelantan, including notices, notifications, and recommendations. The findings indicate that the current laws have not effectively addressed the issue of prostitution in Malaysia generally and in Kelantan specifically. Therefore, non-legal measures by the government, non-governmental organizations, and the society must complement existing laws to better address this issue.Keywords: Registration of Guest Act 1965, prostitution, Women and Girls Protection Act 1973, Kelantan, Majlis Agama Islam dan Istiadat Melayu Kelantan, brothelFull Text: PDF